Biocatalytic assembly of chemically modified oligonucleotides. (16th March 2022) - Mann, Greg; Stanger, Frédéric V.; Peschke, Theo; Schroer, Kirsten; Trung, Nhat Quang Nguyen; Burrer, Nathalie; Grassinger, Franziska; Piccioni, Lorenzo; Erdogan, Oemer; Heimburger, Jeremy; Koehl, Hervé; Ertle, Heike; et al.
Graphical abstract: Abstract: With renewed interest in therapeutic oligonucleotides, and at the same time the pharmaceutical industry set itself ambitious sustainability goals, there is a strong interest to investigate next-generation synthesis methods for these highly modified oligonucleotides. We herein report an RNA ligase catalyzed assembly of multiple, short oligonucleotides in aqueous solution to generate an siRNA product. A conversion of the non-native substrates to the desired product of 40 – 80 % was achieved.